2015
DOI: 10.1007/s00122-014-2432-6
|View full text |Cite
|
Sign up to set email alerts
|

qAC2, a novel QTL that interacts with Wx and controls the low amylose content in rice (Oryza sativa L.)

Abstract: This manuscript reports the fine mapping of a novel QTL, qAC2 controlling the low amylose in rice. The action mechanism of the qAC2 is also investigated by the analysis of genetic interactions to Wx (a), Wx (b), du1, du2 and du3. Amylose content of the rice (Oryza sativa L.) endosperm greatly affects starch properties and eating quality of cooked rice. Seeds of japonica rice cultivar Kuiku162 have low amylose content (AC) and good eating quality. Our analysis revealed a novel QTL, designated as qAC2 that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…In this study, we identified 93 QTL in the whole population at multiple field locations with different environmental conditions, and we detected four stable pleiotropic regions on chromosomes 2, 6, 7 and 11, while we detected the unstable and minor QTL on other chromosomes. In agreement with previous studies (Aluko et al., ; Li et al., ; Sano et al., ; Takemoto‐Kuno et al., ; Zhang et al., ), these QTL were detected on chromosomes 2 and 6, these QTL cluster to the major qAC2 , Wx and ALK or qGC6 . At the same time, we also detected two novel major QTL clusters on chromosomes 7 and 11, temporarily named qRVA7 and qRVA11 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we identified 93 QTL in the whole population at multiple field locations with different environmental conditions, and we detected four stable pleiotropic regions on chromosomes 2, 6, 7 and 11, while we detected the unstable and minor QTL on other chromosomes. In agreement with previous studies (Aluko et al., ; Li et al., ; Sano et al., ; Takemoto‐Kuno et al., ; Zhang et al., ), these QTL were detected on chromosomes 2 and 6, these QTL cluster to the major qAC2 , Wx and ALK or qGC6 . At the same time, we also detected two novel major QTL clusters on chromosomes 7 and 11, temporarily named qRVA7 and qRVA11 .…”
Section: Discussionsupporting
confidence: 92%
“…Based on molecular marker linkage maps and genome sequencing data, many genes and QTL related to quality traits (mainly appearance and grain size) have been identified and exploited in rice (Xing & Zhang, ); these genes/QTL include GW2 , GS2 , GS3 , GS5 , GW5 , GW6 and GL7 (Fan et al., ; Hu et al., ; Song, Huang, Shi, Zhu, & Lin, ; Wang, Li et al., ; Wang, Xiong et al., ; Weng et al., ; Xu, Liu et al., ). In contrast, only a few rice genes and QTL related to milling, nutrition and cooking and eating quality have been cloned ( Wx , qAC2 , qGC6 , ALK , Chlalk5 and Du1 ) (He et al., ; Li et al., , ; Sano, Katsumata, & Okuno, ; Takemoto‐Kuno et al., ; Zeng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in addition to the Wx gene, single-base mutations in other genes also can cause changes in AAC (Ando et al, 2010;Takemoto et al, 2015) . The reasons for changes in composition of endosperm starch are multifaceted, and the genetic basis of the material was the primary cause.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, further studies are needed to discern whether this difference has a genetic basis. Previous studies have shown that in addition to the Wx gene, single-base mutations in other genes also can cause changes in AAC (Ando et al, 2010;Takemoto et al, 2015) . Second, the difference in starch composition was also related to different developmental conditions and the ambient temperature.…”
Section: Differences In Endosperm Composition Of Superior and Infermentioning
confidence: 99%
“…Accurate understanding of the genetic structure and genes controlling virulence is required in management strategies for the durability of blast resistance in rice. Japanese market (Ando et al 2010, Sato et al 2002, Takemoto-Kuno et al 2015. The market in Japan evaluates rice products based on these traits.…”
Section: Premium Traitsmentioning
confidence: 99%